1999
DOI: 10.1021/jp991258i
|View full text |Cite
|
Sign up to set email alerts
|

FTIR-ATR Studies of the Hydration of 15-Crown-5 and 18-Crown-6 in Aqueous Solutions

Abstract: The hydration of 15-crown-5 (15C5) and 18-crown-6 (18C6) in aqueous solutions has been studied by FTIR-ATR spectroscopy. A model of decomposition of the O−H stretching band of water into four components, accounting for bound and bulk water in the solutions, has been employed in the analysis of the spectra. The dependencies of the relative areas and peak wavenumbers of the resolved components on concentration reveal similarities and differences in the hydration of the two crown ethers. The number of water molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(46 citation statements)
references
References 42 publications
7
38
1
Order By: Relevance
“…This conclusion was supported by recent IR spectral studies. 32,33 In contrast with the result in water, our results suggest that the dominant species of B18C6 is the monohydrated one in the water saturated-CF, DCM, 1,2-DCE and NB. Since the nH2O,L value seems to converge at almost 0.8 in spite of change in cH2O,S,o, the higher hydration may occur only slightly or with much difficulty in these solvents.…”
Section: Hydration Number Of Free B15c5 and B18c6contrasting
confidence: 99%
See 2 more Smart Citations
“…This conclusion was supported by recent IR spectral studies. 32,33 In contrast with the result in water, our results suggest that the dominant species of B18C6 is the monohydrated one in the water saturated-CF, DCM, 1,2-DCE and NB. Since the nH2O,L value seems to converge at almost 0.8 in spite of change in cH2O,S,o, the higher hydration may occur only slightly or with much difficulty in these solvents.…”
Section: Hydration Number Of Free B15c5 and B18c6contrasting
confidence: 99%
“…Nickolov et al 32 investigated the hydration of 15C5 and 18C6 in water by IR spectroscopy, and concluded that 18C6 is strongly hydrated by doubly hydrogen-bonded water molecules, while 15C5 is hydrated mostly by single hydrogen-bonded water molecules, in which the water molecules stay outside the crown planar ring. The size of the water molecule (diameter of approximately 2.8 Å, if one assumes a sphere) 44 agrees with the cavity size of 18-membered ring crown ether (2.9 ± 0.3 Å) 45 and is too large for that of 15-membered ring crown ether (2.0 ± 0.2 Å).…”
Section: Hydration Number Of Free B15c5 and B18c6mentioning
confidence: 99%
See 1 more Smart Citation
“…The second is at 10-20 mol ratio upward and is characterized with almost constant values of the relative areas of bulk water. The transition between the two ranges or more particularly the two mole ratios gives the maximum number of water molecules associated per IL molecule [49]. Figs.…”
Section: Tablementioning
confidence: 99%
“…Nevertheless, Raman and IR O-H stretching spectra of the solutions indicate that a significant part of the water molecules still participate in tetrahedral structural units and have hydrogen bonding similar to the one in liquid water. [3][4][5] Therefore, an assumption that water molecules have a definite affinity to form clusters in moderately concentrated solutions of POE can be inferred. Taking into account the compact structure of the solutions at these concentrations, the water clusters should be relatively small and homogeneously distributed with no large domains of bulk water being present in the solutions.…”
Section: Hydration Of Poly(oxyethylene) At Intermediate Concentrationsmentioning
confidence: 99%